PEMANFAATAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN MEMBACA IQRA PADA ANAK USIA DINI DI TADIKA TINTA KHALIFAH SUNGAI KARANGAN, MALAYSIA - Hayati, Nur; Harfiani, Rizka (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Education is an important means of achieving optimal learning outcomes, so in this case it is prohibited to ignore the important components involved in learning. One example of a learning media component that cannot be overlooked is the use of learning media. This writing aims to analyze the use of audio-visual media in increasing motivation to learn to read iqra' in early childhood in Tadika Tinta Khalifah Sungai Karangan, Malaysia. The research used a qualitative approach with data collection techniques through interviews and observation. The research was implemented at Tadika Tinta Khalifah Sungai Karangan, Malaysia for 1 month. The results obtained are learning carried out by utilizing audio-visual media can generate motivation for children, so that children will be more excited and interested in learning. Because audiovisual media is one of the media that combines images with sound. Examples of the utilization of audio-visual media can be implemented in the form of films, videos, and so on. The conclusion is that in learning to read at an early age level, especially in reading iqro' can be done by utilizing audio-visual learning media.